Narrow-winged pyralids (Lepidoptera, Pyraloidea, Pyralidae, Phycitinae) of Leningrad Province and the city of St. Petersburg, Russia - Tsvetkov, Eugene (Zootaxa, 2020)
An annotated list of 50 species of narrow-winged pyralids is provided, including the species, which were ever recorded in Leningrad Province and the city of St. Petersburg. Eleven species are new for the region, among them 6 species which are new for Northwest region of Russia; one species, Ephestia mistralella (Millière, 1874), is reported for Russia for the first time.